Biochemical Changes and Plasma Level of Lipoprotein-Associated Phospholipase A2 in Patients with and without Coronary Artery Disease: A Cross-Sectional Study - Bahaedin Ben-Mahmud; Abdulmunam Fellah; Khaloud Essokni (AlQalam Journal of Medical and Applied Sciences, 2024)
Coronary artery disease (CAD) is the leading cause of death worldwide. the aim of study is to evaluate the association between plasma lipoprotein-associated phospholipase A2 (Lp-PLA2) and the clinical and biochemical risk factors for CAD among Libyan individuals. This cross-sectional study to evaluate plasma concentration of Lp-PLA2 between patients with CAD and those without CAD in both genders based on clinical history, exercise ECG, two-dimensional echocardiography, and coronary angiography. Several biochemical parameters were estimated. Plasma levels of Lp-PLA2 were measured. A total of 181 individuals were recruited for this study, involving 125 with CAD and 56 without CAD. Plasma Lp-PLA2 concentration was significantly higher in patients with CAD versus individuals without coronary artery disease. In addition, the plasma concentration of Lp-PLA2 was higher in patients >60 years of age compared with patients <60 years old. To conclude that Plasma level of Lp-PLA2 concentration was independently correlated with CAD, inflammatory marker such as high sensitivity C-reactive protein among Libyan patients. مرض الشريان التاجي هو السبب الرئيسي للوفاة في جميع أنحاء العالم والهدف من الدراسة هو تقييم العلاقة بين فسفوليباز أ2 المرتبط بالبروتين الدهني في البلازما وعوامل الخطر السريرية والكيمائية الحيوية لمرض الشريان التاجي لدى الأفراد الليبيين. ميز هذا التحقيق المقطعي بين المرضى الذين يعانون من مرض الشريان التاجي وأولئك الذين لا يعانون من مرض الشريان التاجي في كلا الجنسين على أساس التاريخ السريري، تخطيط القلب القياسي، تخطيط القلب بالإجهاد، تخطيط صدى القلب ثنائي الأبعاد، وتصوير الأوعية التاجية. تم جمع العديد من بيانات المؤشرات البيو كيميائية. تم تحديد مستويات فسفوليباز أ2 المرتبط بالبروتين الدهني في البلازما بواسطة مقايسة الامتصاص المناعي المرتبط بالإنزيم. تم جمع 181 فردًا في هذه الدراسة، منهم 125 مصابًا بمرض الشريان التاجي و56 شخصًا بدون مرض الشريان التاجي. كان تركيز فسفوليباز أ2 المرتبط بالبروتين الدهني في البلازما أعلى بشكل ملحوظ في المرضى الذين يعانون من مرض الشريان التاجي مقابل الأفراد الذين لا يعانون من مرض الشريان التاجي (270 ± 9.2 مقابل 162.2 ± 11.8 نانو غرام / مل؛ P <0.0001 على التوالي)، وخاصة بين المرضى الذين يخضعون لتطعيم مجازة الشريان التاجي مقابل المرضى الذين يعانون من مرض الشريان التاجي. كانوا على العلاج الطبي والتدخل التاجي عن طريق الجلد (P <0.0001)، على التوالي. بالإضافة إلى ذلك، كان تركيز البلازما لفسفوليباز أ2 المرتبط بالبروتين الدهني أعلى في المرضى الذين تزيد أعمارهم عن 60 عامًا مقارنةً بالمرضى الذين تقل أعمارهم عن 60 عامًا (207.9 ± 12.6 مقابل 260.1 ± 10.4؛ P <0.002). ارتبط مستوى تركيز فسفوليباز أ2 المرتبط بالبروتين الدهني في البلازما بشكل مستقل بمرض الشريان التاجي، وهو علامة التهابية مرتبطة بشكل كبير ببروتينات C التفاعلية، والفئة العمرية الأكبر من 60 عامًا لدى المرضى الليبيين